2016
DOI: 10.5796/electrochemistry.84.674
|View full text |Cite
|
Sign up to set email alerts
|

Categorizing Molten Salt Complexes as Ionic Liquids and Their Applications to Battery Electrolytes

Abstract: Certain stoichiometric mixtures of salts and solvents (ligands) yield a salt complex. Salt complexes that are low melting and consist of discrete complex ions and their counter ions in the molten state can together form the essence of an ionic liquid (IL). This stable complex melt can now be categorized into a new subclass of ionic liquids, "solvate (or chelate) ILs." In this paper, we describe the current criteria for this new family of ILs. Concentrated mixtures of lithium salts and oligoether solvents are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…90 Another study comparing several equimolar mixtures of either G 3 or G 4 with various salts (LiBETI, LiBF 4 , LiTf and LiNO 3 ) revealed that the dissolution of lithium polysulfides may be suppressed whether SILs are employed. 91 On the other hand, the G 4 -LiTf solution with the lithium salt in a 1 mol kg −1 concentration was considered the preferred electrolyte for performing a comparative evaluation of the electrochemical performance of several cathode composites prepared by mixing sulfur with carbon materials of various natures (namely, graphite, mesocarbon microbeads, and multi-walled carbon nanotubes). Besides, the electrolyte characteristics in terms of 1 H, 7 Li, and 19 F nuclei self-diffusion coefficients, ionic conductivity, and ionic association degree were investigated by combining NMR and impedance spectroscopy measurements.…”
Section: "Glyme Electrolyte" In Li-s Cell: a Battery Close To Practical Applicationsmentioning
confidence: 99%
“…90 Another study comparing several equimolar mixtures of either G 3 or G 4 with various salts (LiBETI, LiBF 4 , LiTf and LiNO 3 ) revealed that the dissolution of lithium polysulfides may be suppressed whether SILs are employed. 91 On the other hand, the G 4 -LiTf solution with the lithium salt in a 1 mol kg −1 concentration was considered the preferred electrolyte for performing a comparative evaluation of the electrochemical performance of several cathode composites prepared by mixing sulfur with carbon materials of various natures (namely, graphite, mesocarbon microbeads, and multi-walled carbon nanotubes). Besides, the electrolyte characteristics in terms of 1 H, 7 Li, and 19 F nuclei self-diffusion coefficients, ionic conductivity, and ionic association degree were investigated by combining NMR and impedance spectroscopy measurements.…”
Section: "Glyme Electrolyte" In Li-s Cell: a Battery Close To Practical Applicationsmentioning
confidence: 99%
“…The thermal properties (T g , T m , and 4 ] also raises the possibility that a FeBr 3 -G3 adduct was formed in the decomposition process at high temperature. The Lewis acid-base complex may be responsible for the highly elevated evaporation temperature of G3.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…To avoid shuttling of the redox active anions between the electrodes, a lithium-ion conducting glass-ceramic (OHARA, LICGC, 19 mm in diameter) was also used. 4 ]-based catholyte cell was assembled in the Ar-filled grove box. The galvanostatic charge/ discharge measurements were performed with an automatic charge/ discharge instrument (HJ1001SM8A, Hokuto Denko) at 30°C.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…sub-class of ionic liquids, solvate ionic liquids, have begun to be viewed as another set of potential electrolyte candidates. [7][8][9][10] In these ionic liquids the traditional bulky organic cation is replaced with a long-lived complex consisting of an atomic metal cation bound to solvent. In most cases this complex consists of the metal cation and a single polydentate solvent molecule.…”
mentioning
confidence: 99%